RANCANG BANGUN ALAT PENYAMBUNG DAN PEMUTUS SUPLAI LISTRIK DENGAN MENGGUNAKAN RFID (RADIO FREQUENCY IDENTIFICATION) DAN SMS GATEWAY BERBASIS ARDUINO - Januar Arief Rachman; Jumiyatun Jumiyatun; Sari Dewi (Foristek, 2020)
Electricity demand is increasing with the development of technology in various fields, such as agriculture, medicine, automotive and others. But for controlling electricity in a room or building there are still found to be less efficient. In controlling electricity or remote control using SMS need to pay attention to the signal that is on the SIM800L sms module. The way to get a signal is the need for power supply above 2 amperes for this SIM800L module. This final project produces a tool that can control electricity in a room that is connecting and disconnecting the electricity supply using an RFID card which can turn on and off each room, even more than two outputs at once, and use SMS media for remote control.